Molecular studies in children with fragile X syndrome - S., Manjula Thulasi (International Journal of Research in Medical Sciences, 2017)
Background: Fragile X Syndrome (FXS) is the most common single gene cause of Learning (intellectual) Disability (LD). FMR1 gene mutation is the commonest cause for this syndrome. The present study aims to analyze the incidence of the syndrome in Kerala population. Methods: Study was conducted among 86 children belonging to different places of Kerala. Children were selected on the basis of IQ scores and typical features of FXS. Blood samples were taken and routine karyotype was performed. PCR analyses were also conducted. Results: Majority of the children showed typical features of FXS. Out of 86 samples, six showed chromosomal aberrations were excluded. PCR analyses in 55 samples, screened 35 samples with FMR1 mutation, in which 26 samples having pre- mutation and 9 samples with full mutation. Conclusions: Through this genetic study, differential diagnosis of LD children with FXS, LD children with constitutional chromosome abnormalities, and LD children without any apparent genetic abnormalities could be established.